2017
DOI: 10.1248/bpb.b17-00015
|View full text |Cite
|
Sign up to set email alerts
|

A C<sub>8</sub>-Modified Graphene@mSiO<sub>2</sub> Composites Based Method for Quantification of Gallic Acid in Rat Plasma after Oral Administration of Changtai Granule and Its Application to Pharmacokinetics

Abstract: A rapid, effective extraction technique has been established for measuring the gallic acid in rat plasma by using sandwich-structured graphene/mesoporous silica composites with C-modified interior pore-walls as adsorbent. The unique characteristics of the graphene-silica composites excluded large molecules, like proteins, from the mesopore channels as a result of size exclusion effect, leading to a direct extraction of drug molecules from protein-rich biological samples such as plasma without any other pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The authors reported that a Paclitaxel/GA combination could represent a promising alternative with lower side effects for Paclitaxel/Carboplatin combinations in treatment of cervical cancer. Recent pharmacokinetic human and animal clinical studies were based on Chinese GA-based patented medicines but further investigation is needed on the GA kinetic profile after dietary supplementation before drawing any conclusion for its efficacy against pathological conditions [105]. Paolini et al (2015) [106] performed a study to explore the potential of GA as a promising new anticancer drug.…”
Section: Gallic Acidmentioning
confidence: 99%
“…The authors reported that a Paclitaxel/GA combination could represent a promising alternative with lower side effects for Paclitaxel/Carboplatin combinations in treatment of cervical cancer. Recent pharmacokinetic human and animal clinical studies were based on Chinese GA-based patented medicines but further investigation is needed on the GA kinetic profile after dietary supplementation before drawing any conclusion for its efficacy against pathological conditions [105]. Paolini et al (2015) [106] performed a study to explore the potential of GA as a promising new anticancer drug.…”
Section: Gallic Acidmentioning
confidence: 99%
“…Gallic acid is an endogenous polyphenol found abundantly in medicinal plant. In recent years, some pharmacokinetic studies on crude drugs and/or Chinese patented medicines which content GA has been performed on healthy volunteers ( Shahrzad and Bitsch, 1998 ) and normal animals ( Xu et al, 2017 ; Zhu et al, 2017 ). However, considerable uncertainty remains due to the lack of comprehensive kinetic profiles after administration of GA monomer in vivo , especially under pathological condition.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently with the extensive research into the cardioprotective activities of GA, a few reports had addressed the disposition profiles of GA in vivo . C8-modified graphene@mSiO2 composites based method and UPLC–MS/MS method have been applied to the kinetic studies of GA ( Ma et al, 2015 ; Xu et al, 2017 ; Zhu et al, 2017 ). However, most of these work were carried out with the administration of crude drugs and/or Chinese patented medicines which content GA. Only in a few work, e.g., the previous studies of Shahrzad and Bitsch (1998) , Yasuda et al (2000) , and Shahrzad et al (2001) , metabolic and primary pharmacokinetic properties of GA were studied with high-performance liquid chromatography (HPLC) methods after oral administration of GA monomer.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we have compared polyherbal nanoparticle study with a polyherbal extract containing both the biomolecules, utilized 100mg/kg of gallic acid and quercetin in nanoformulation which was lower than the polyherbal extract containing gallic acid and quercetin 400 mg/kg here all data summarized in table no 2. [29]…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%